2021
DOI: 10.1108/ijtc-09-2020-0176
|View full text |Cite
|
Sign up to set email alerts
|

Memorable experience, tourist-destination identification and destination love

Abstract: Purpose This paper aims to investigate the impact of memorable destination experience and destination attractiveness on tourist-destination identification and destination love. It also investigates the moderating role of gender. Design/methodology/approach Using the cluster sampling method, the study selected cities of a developing country with the most popular destinations. A questionnaire survey was used to collect data from a sample of foreign and domestic tourists. To test the research model, a covarianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 90 publications
3
22
0
Order By: Relevance
“…Hwang et al (2021) concluded that brand experience has an indirect effect on brand identification through brand satisfaction. Shafiee et al (2021) studied memorable destination experiences and found that such experiences engender the destination identity. From the customer and brand relationship perspective, Kumar and Kaushik (2020) identified that various brand experiences have a determining influence on the brand identification with a product or service brand.…”
Section: 73mentioning
confidence: 99%
“…Hwang et al (2021) concluded that brand experience has an indirect effect on brand identification through brand satisfaction. Shafiee et al (2021) studied memorable destination experiences and found that such experiences engender the destination identity. From the customer and brand relationship perspective, Kumar and Kaushik (2020) identified that various brand experiences have a determining influence on the brand identification with a product or service brand.…”
Section: 73mentioning
confidence: 99%
“…Affective experiences can be mild and intense (Beckman et al, 2013); they can be positive (e.g. joy, happiness, love, excitement, romantic and contentment) or negative (frustration, anger and JPMD 17,1 disgust) (Shafiee et al, 2021;Trauer and Ryan, 2005). They are at the heart of place experience because people long for emotional or hedonic experiences (Lugosi and Walls, 2013).…”
Section: Unpacking the Facets Intention And Intensity Of Place Experi...mentioning
confidence: 99%
“…Spectacular experiences also include housed iconic attractions and buildings (Maitland, 2010). These experiences are important because they make places more memorable and successful Assessing place experiences (Hudson and Ritchie, 2009;Shafiee et al, 2021). Indeed, not all experiences are spectacular; many experiences are mundane, banal and quotidian (Edensor, 2007;Lugosi and Walls, 2013).…”
Section: Unpacking the Facets Intention And Intensity Of Place Experi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Memorable and positive experiences are closely related to behavior, consumption decisions, evaluation, trust, and preferences of consumers (Braun-LaTour et al, 2007; Lechner & Paul, 2019; Ratnayake et al, 2010). Memorable experience is an essential element in creating value in the tourism industry (Cornelisse, 2018; Mittal et al, 2022; Shafiee et al, 2021; Williams, 2006). For tourists to feel satisfied, they should feel positive emotions that lead to memorable experiences, which in turn impact their decision making process in the future (Chandralal & Valenzuela, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%